White electroluminescence from SiNx thin films by a PECVD equipment using dichlorosilane precursor and study of emission mechanism. (14th October 2020) - Ortiz-Santos, A.; Ramos, C.; Sastré-Hernández, J.; Santana, G.; Dutt, A.
ABSTRACT: In the present work SiNx  thin films, grown by PECVD technique using dichlorosilane, were used in electroluminescent device (EL) structure. Series of experiments were carried out by varying the flow of H2  and SiH2 Cl2,   and after all the depositions and subsequent result analysis, a set of conditions were identified as M1, M2, M3, and M4 according to the physical thickness of the samples, their PL emission color and intensity of the emission. M3 and M4 conditions were identified as of key interest because of their intense whiteemission. After the photoluminescence (PL) analysis, EL was carried out, and a device structure was fabricated for the study. Role of quantum confinement effect was found for the white emission from the calculated nanocrystals from 2.5 to 5 nm. These results could be an important step for the establishment of optoelectronic devices such as silicon LEDs in the near future.